Akebia trifoliata pericarp extract ameliorates inflammation through NF-κB/MAPK signaling pathways and modifies gut microbiota. Issue 5 (14th May 2020) - Wang, Xiaoya; Yu, Ningxiang; Wang, Zhongliang; Qiu, Tingting; Jiang, Li; Zhu, Xuemei; Sun, Yong; Xiong, Hua
Abstract : Akebia trifoliata fruits, a kind of popular edible berry in Asia, are widely consumed as daily fruits or functional foods. Abstract : Akebia trifoliata fruits, a kind of popular edible berry in Asia, are widely consumed as daily fruits or functional foods. Our previous study found several bioactives from Akebia trifoliata pericarp extract (APE), and preliminarily investigated their anti-inflammatory activity. However, the underlying mechanism of APE for the observed anti-inflammatory effects is still unknown. Thus, the bioactive profiles and anti-inflammatory mechanism of APE were investigated by a combination of chemical assays: UPLC-LTQ-Orbitrap/MS technique, lipopolysaccharide (LPS)-induced RAW264.7 cells and DSS-induced mouse model. The results indicated that the phenolic acids and terpenoids are major bioactives of APE, which could inhibit the production of nitric oxide (NO) and prostaglandin E2 (PGE2 ) by blocking the expression of inducible nitric oxide synthase (iNOS) and cyclooxygenase-2 (COX-2) in RAW264.7 cells as well as reduce the expression of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6), and interleukin-1β (IL-1β), and suppress the phosphorylation of p-65, IκBα and mitogen-activated protein kinase (MAPKs including p38, ERKs, JNKs) proteins both in vitro and in vivo . Furthermore, APE treatment could regulate gut microbiota by increasing the richness of Rikenellaceae and Lactobacillaceae and reducing that of Lachnospiraceae and Ruminococcaceae . In summary, these findings clearly demonstrated that APE mitigates inflammation by restraining the production of cytokines through nuclear factor-κB (NF-κB) and MAPK signaling pathways, and altering gut microbiota, and therefore, this could be a potential functional food for the treatment and prevention of inflammatory bowel diseases.